Sociocultural framing of ‘ambo-gbabe’ music video campaign in the 2015 gubernatorial elections in Lagos State, Nigeria (2018)
The 2015 Lagos State governorship campaign of the All Progressives Congress (APC) used sociocultural frames conjuring indigeneity and modernity to attract political attention and support. Constructed through religious, economic, cultural and human-interest frames, a blissful future encapsulating the hopeful ethos of the city was projected. Reflecting and conscientizing their messianic aspirations, this existentialist paradigm attended to the hopes of the people for better living conditions. The article examines and interprets the sociocultural frames in ‘Ambo-Gbabe’ music video, focusing on context-specific images that reveal the manifesto of Akinwunmi Ambode. The video expressed the political ideas and intentions of the contestant by employing popular, emotional and cultural appeals. A combination of figurative expressions, languages, proverbs, dramaturgy, incantation, rap, and skelewu and shoki dances drew the message closer to the political environment, while the musicology relates to the demographic ecology of Lagos. Using the genre of current street music, the candidate’s political vision of populism, collectivism, gender equality and unity in diversity were showcased. The lyrics, sounds and imageries largely conform to the sociodemographic and cultural ideologies of residents. The paper portrays the place of ethnomusicology for political campaign and convergence between politics and performance in popular culture.